The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/acs.jafc.5b02181
|View full text |Cite
|
Sign up to set email alerts
|

Cyanidin-3-O-β-glucoside Purified from Black Rice Protects Mice against Hepatic Fibrosis Induced by Carbon Tetrachloride via Inhibiting Hepatic Stellate Cell Activation

Abstract: This study investigated whether cyanidin-3-O-β-glucoside (Cy-3-G), a predominant anthocyanin, could exert a protective role on liver injury and its further mechanisms of the anti-fibrosis actions in mice. The results demonstrated that the treatment of Cy-3-G (800 mg/kg diet) for 8 weeks significantly attenuated hepatotoxicity and fibrosis in carbon tetrachloride (CCl4) administered mice. Cy-3-G strongly down-regulated the expression of α-smooth muscle actin (α-SMA), desmin, and matrix metalloproteinase (MMPs),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…Extraction and purification of Cy-3-g from black rice was performed as described previously (16). Briefly, highly purified Cy-3-g was isolated from black rice using middle-pressure liquid chromatography (MPLC).…”
Section: Methodsmentioning
confidence: 99%
“…Extraction and purification of Cy-3-g from black rice was performed as described previously (16). Briefly, highly purified Cy-3-g was isolated from black rice using middle-pressure liquid chromatography (MPLC).…”
Section: Methodsmentioning
confidence: 99%
“…Other natural anti-adipogenic substances, like cyanidin and carvacrol, Pompei et al (2012) and Spalletta et al (2018) may also restrain adipose tissue fibrosis, as recently seen for liver fibrosis. In particular cyanidin has been proven to be effective in antagonizing the oxidative stress, the inflammatory response and HSC activation; while carvacrol has been found to be particularly successful in inhibiting the TGFβ signaling pathway, by downregulating not only the TGF-β levels but also the protein levels of the related Hippo cascade mediators such as TAZ and YAP (Cho et al, 2014;Jiang et al, 2015;Hussein et al, 2017;Mohseni et al, 2019). Blockade of these signaling pathways could inhibit EMT and ameliorate fat fibrosis, as well as the associated metabolic dysfunctions such as insulin resistance.…”
Section: Adipose Tissue Fibrosismentioning
confidence: 99%
“…A series of studies from Ling's team suggested that 800 mg/kg dietary cyanidin-3-O- β -glucoside alleviated liver fibrosis by suppressing inflammatory factors, such as TNF- α , IL-6, and IL-10. The progression of HSC activation was also blocked by cyanidin-3-O- β -glucoside through significant inhibition of HSC proliferation and migration [ 111 , 112 ].…”
Section: Flavonoidsmentioning
confidence: 99%